Tabletop Application of SALT Triage to 10, 100, and 1000 Pediatric Victims. Issue 2 (14th February 2020) - McGlynn, Nicholas; Claudius, Ilene; Kaji, Amy H.; Fisher, Emilia H.; Shaban, Alaa; Cicero, Mark X.; Santillanes, Genevieve; Gausche-Hill, Marianne; Chang, Todd P.; Donofrio-Odmann, J. Joelle
Abstract: Introduction: The Sort, Access, Life-saving interventions, Treatment and/or Triage (SALT) mass-casualty incident (MCI) algorithm is unique in that it includes two subjective questions during the triage process: "Is the victim likely to survive given the resources?" and "Is the injury minor?" Hypothesis/Problem: Given this subjectivity, it was hypothesized that as casualties increase, the inter-rater reliability (IRR) of the tool would decline, due to an increase in the number of patients triaged as Minor and Expectant. Methods: A pre-collected dataset of pediatric trauma patients age <14 years from a single Level 1 trauma center was used to generate "patients." Three trained raters triaged each patient using SALT as if they were in each of the following scenarios: 10, 100, and 1, 000 victim MCIs. Cohen's kappa test was used to evaluate IRR between the raters in each of the scenarios. Results: A total of 247 patients were available for triage. The kappas were consistently "poor" to "fair:" 0.37 to 0.59 in the 10-victim scenario; 0.13 to 0.36 in the 100-victim scenario; and 0.05 to 0.36 in the 1, 000-victim scenario. There was an increasing percentage of subjects triaged Minor as the number of estimated victims increased: 27.8% increase from 10- to 100-victim scenario and 7.0% increase from 100- to 1, 000-victim scenario. Expectant triage categorization of patients remained stable as victim numbers increased. Conclusion: Overall, SALT demonstrated poor IRR in this study of increasing casualty counts while triaging pediatric patients. Increased casualty counts in the scenarios did lead to increased Minor but not Expectant categorizations.